Pengaruh Kualitas Pelayanan, Kepuasan Dan Costumer Relationship Marketing Terhadap Loyalitas Nasabah Di Bank BMI KCP Ponorogo - dian puspitasari; Ajeng Pipit Fitriani (JOURNAL OF SHARIA ECONOMICS, 2024)
Today, competition in the corporate world, particularly banking, is increasingly tight and intense.. Customer loyalty should be the highest target that must be built and achieved by management in banking, especially sharia banking. This is because the level of competition between Islamic financial institutions is getting tighter. This research is motivated by the problem of customer loyalty at Bank Muamalat KCP Ponorogo. The purpose of this research is to determine the influence of service quality, satisfaction and CRM on customer loyalty at Bank Muamalat KCP Ponorogo This research uses quantitative research methods. The data collection method uses a questionnaire distributed to Bank Muamalat KCP Ponorogo customers totaling 100 respondents using an incidental sampling technique. The data analysis tools used in this research are validity and reliability tests, classical assumption tests, multiple regression analysis consisting of the t test, F test, and coefficient of determination test which are processed using the SPSS Statistics 22 tool. The results of this research based on the t test show that the service quality variable has a positive and significant effect on customer loyalty. The satisfaction variable has no effect on customer loyalty, the customer relationship marketing variable has a positive and significant effect on customer loyalty. Based on the F test, it shows that the variables of service quality, satisfaction and customer relationship marketing simultaneously influence customer loyalty.